The cost of managing complex surgical site infections following primary hip and knee arthroplasty: A population-based cohort study in Alberta, Canada. (10th September 2018) - Rennert-May, Elissa D.; Conly, John; Smith, Stephanie; Puloski, Shannon; Henderson, Elizabeth; Au, Flora; Manns, Braden
Abstract: Objective: Nearly 800, 000 primary hip and knee arthroplasty procedures are performed annually in North America. Approximately 1% of these are complicated by a complex surgical site infection (SSI), leading to very high healthcare costs. However, population-based studies to properly estimate the economic burden are lacking. We aimed to address this knowledge gap. Design: Economic burden study. Methods: Using administrative health and clinical databases, we created a cohort of all patients in Alberta, Canada, who received a primary hip or knee arthroplasty between April 1, 2012, and March 31, 2015. All patients who developed a complex SSI postoperatively were identified through a provincial infection prevention and control database. A combination of corporate microcosting data and gross costing methods were used to determine total mean 12- and 24-month costs, enabling comparison of costs between the infected and noninfected patients. Results: Mean 12-month total costs were significantly greater in patients who developed a complex SSI compared to those who did not (CAD$95, 321 [US$68, 150] vs CAD$19, 893 [US$14, 223]; P < .001). The magnitude of the cost difference persisted even after controlling for underlying patient factors. The most commonly identified causative pathogen (38%) was Staphylococcus aureus (95% MSSA). Conclusions: Complex SSIs following hip and knee arthroplasty lead to high healthcare costs, which are expected to rise as the yearly number of surgeries increases. Using our costing estimates, the cost-effectiveness of different strategies to prevent SSIs should be investigated.